IL-33 Initiates Vascular Remodelling in Hypoxic Pulmonary Hypertension by up-Regulating HIF-1α and VEGF Expression in Vascular Endothelial Cells - Liu, Jie; Wang, Wang; Wang, Lei; Chen, Shihao; Tian, Bo; Huang, Kewu; Corrigan, Chris J.; Ying, Sun; Wang, Wei; Wang, Chen (EBioMedicine, 2018)
IL-33 may play a role in the vascular remodelling of hypoxic pulmonary hypertension (PH) but the precise mechanisms are still unclear. We hypothesized that hypoxia promotes expression of IL-33 and its receptor ST2 on vascular endothelial cells, which in turn leads to dysfunction of vascular endothelial cells and smooth muscle cells contributing to PH. Immunohistochemistry showed that immunoreactivity for IL-33 and ST2 was significantly increased in lung tissue of murine model of hypoxia-induced PH (HPH) and of subjects with bronchiectasis-PH. trans-Thoracic echocardiography showed that haemodynamic changes and right ventricular hypertrophy associated with HPH were significantly abrogated in St2−/− compared with WT mice. Administration of IL-33 further exacerbated these changes in the hypoxia-exposed WT mice. In vitro, hypoxia significantly increased IL-33/ST2 expression by human pulmonary arterial endothelial cells (HPAECs), while exogenous IL-33 enhanced proliferation, adhesiveness and spontaneous angiogenesis of HPAECs. Knockdown of endogenous Il33 or St2 using siRNA transfection significantly suppressed these effects in both normoxic and hypoxic culture-conditions. Deletion of the St2 gene attenuated hypoxia-induced, elevated lung expression of HIF-1α/VEGFA/VEGFR-2/ICAM-1, while administration of exogenous VEGFA partially reversed the attenuation of the haemodynamic indices of PH. Correspondingly, knockdown of the St2 or Hif1α genes almost completely abrogated IL-33-induced expression of HIF-1α/VEGFA/VEGFR-2 by HPAECs in vitro. Further, IL-33-induced angiogenesis by HPAECs was extensively abrogated by knockdown of the Hif1α/Vegfa or Vegfr2 genes. These data suggest that hypoxia induces elevated expression of IL-33/ST2 by HPAECs which, at least partly by increasing downstream expression of HIF-1α and VEGF initiates vascular remodelling resulting in HPH. •Evidence before this study•We have been focusing on the role of cytokines in the pathogenesis of chronic pulmonary diseases for a long time, including asthma, COPD, fibrosis and bronchiectasis. We and others found that IL-33 might contribute to the occurrence and prognosis of many other diseases through binding its receptor ST2. Based on these findings, we were very eager to know whether IL-33/ST2 axis also exerts a role in hypoxia-induced pulmonary hypertension (HPH), a complication of many chronic respiratory diseases. Although it is well known that HIF-1α and VEGF play critical role in this complication, it is still unclear what the upstream of HIF-1α and VEGF is. Therefore, we first tested immunoreactivity for IL-33 and its receptor ST2 in the lung tissue sections derived from surgical specimens and from our established murine models of HPH. Surprisingly, we noted the increased immunoreactivity for both targets in these tissue sections. These findings inspired us to further explore the details of IL-33/ST2 in the pathogenesis of HPH.•Added value of this study•HPH is a life-threatening complication because there is lack of effective treatment. Although pulmonary arteries and ventricular remodelling might be mainly involved in the pathogenesis of the disease, the precise mechanisms are largely unknown. In the present study, we showed that hypoxia is a critical driver which induced expression of IL-33 and ST2 by endothelial cells. These factors, in turn triggered expression of HIF-1α and VEGF by endothelial cells and led to proliferation, adhesion and tube formation of these cells. We also showed that in the presence of IL-33, endothelial cells were able to affect proliferation and migration of artery smooth muscle cells, although IL-33 alone did not have such effects. These findings suggest that hypoxia and IL-33/ST2 might be initiators for HPH, through regulating downstream factors HIF-1α and VEGF.•Implications of all the available evidence•Our data suggest that IL-33/ST2 axis plays critical role in the pathogenesis of hypoxia-induced pulmonary hypertension because depletion of these molecules much remitted the phenomenon of complication. These observations might provide alternative therapeutic strategy for clinical treatment of HPH.